A promising view to the Moon: Anticipations for Tianwen-2 samples returned from Kamo’oalewa - WenZhe Li; Yong Wei; Jian-Yang Li; Wei Yang (Earth and Planetary Physics)
The exploration of asteroids has received increasing attention since the 1990s because of the unique information these objects contain about the history of the early solar system. Quasi-satellites are a population of asteroids that co-orbit closely with, but are outside the gravitational control of, the planet. So far, only five Earth quasi-satellites have been recognized, among which (469219) Kamo’oalewa (provisionally designated as 2016 HO3) is currently considered the most stable and the closest of these. However, little is known about this particular asteroid or this class of near-Earth asteroids because of the difficulties of observing them. China has announced that Tianwen-2, the asteroid sample-return mission to Kamo’oalewa, will be launched in 2025. Here, we review the current knowledge of Kamo’oalewa in terms of its physical characteristics, dynamic evolution, surface environment, and origin, and we propose possible breakthroughs that the samples could bring concerning the asteroid Kamo’oalewa as an Earth quasi-satellite. Confirming the origin of Kamo’oalewa, from its prevailing provenance as debris of the Moon, could be a promising start to inferring the evolutionary history of the Moon. This history would probably include a more comprehensive view of the lunar farside and the origin of the asymmetry between the two sides of the Moon. Comparing the samples from the Moon and Kamo’oalewa would also provide new insights into the Earth wind.